Evolution of economics and the new pragmatism of Grzegorz W. Kolodko - Maciej Bałtowski (Transformation, Integration and Globalization Economic Research (TIGER), 2017)
The paper refers to Kolodko's new and innovative look at economics and its contemporary aims. The paper is composed of three parts. The first, methodological part includes a discussion of the ultimate aims of economic sciences with the consideration of special features of its subject (economy): its variability, variety, and teleological character. The author rejects the traditional division between positive and normative economics. He introduces the concept of a "good economy" (good economic system), which is then analyzed in part two in the framework of the development of economic thought from Smith and Ricardo, through Marx and Keynes, up to the modern welfare economics. The third part is devoted to the analysis of the key elements of the concept of new pragmatism proposed by G. W. Kolodko. The author focuses on Kolodko's views on the contents and aims of contemporary economics and his understanding of the category of a "good economy". He concludes that the concept of "new pragmatism", which is remote from the main-stream contemporary economics, tries to meet the present needs of the changing world while being well settled in the cognitive current of economics dating back to Smith.
Keywords: 330; the aims of economics; economic systems; positive economics; normative economics